2018
DOI: 10.3892/ol.2018.8680
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and its mechanism in prostate cancer

Abstract: The present study aimed to investigate the expression of tumor protein p53 (p53), and its mechanism of function, in prostate cancer (PC). Small interfering RNA (siRNA) was used to interfere with p53 expression in the PC cell line, DU145. Cell viability and p53 expression were analyzed using cell counting kit-8 (CCK-8) and western blotting. The effects of p53 expression on the proliferation, migration and adhesion abilities of PC cells were analyzed using Cell Counting kit-8, Transwell and adhesion assays. Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…VIM3 and TP53 expression was highest in PC3 cells. TP53 is known to be overexpressed in prostate cancer and knockdown of TP53 results in a slower migration of prostate cancer cells (31). Our research group also showed that VIM3 protein levels increased significantly with increasing biological aggressiveness of human prostate cancer specimens from prostate biopsies/radical prostatectomy specimens (10).…”
Section: Discussionsupporting
confidence: 57%
“…VIM3 and TP53 expression was highest in PC3 cells. TP53 is known to be overexpressed in prostate cancer and knockdown of TP53 results in a slower migration of prostate cancer cells (31). Our research group also showed that VIM3 protein levels increased significantly with increasing biological aggressiveness of human prostate cancer specimens from prostate biopsies/radical prostatectomy specimens (10).…”
Section: Discussionsupporting
confidence: 57%
“…While there is no speci c study focusing on NLRP1 protein expression in lung adenocarcinoma and prostate adenocarcinoma compared to normal tissues, Liang et al reported a substantial increase in NLRP1 protein level in patients with prostate cancer compared to those with prostate hyperplasia. Notably, the protein expression levels of NLRP1 showed a positive correlation with the Gleason score of prostate cancer [43]. Although the NLRP1 RNA expression was downregulated in LUAD and PRAD, the decrease in protein levels in LUAD was anticipated, while the increase in protein levels in PRAD was unexpected.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the downregulation of NLRP1 is correlated with unfavorable DFS in CHOL. Several studies have explored the potential of NLRP1 as a prognostic biomarker in various cancers, including lung adenocarcinoma [39,40,44], gastric cancer [45], prostate cancer [43], pancreatic cancer [46,47], head and neck squamous cell carcinoma [48], and laryngeal carcinoma [49]. Shen et al con rmed that decreased expression of NLRP1 was signi cantly associated with a poor prognosis of LUAD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in p53 cause the cell cycle to be dysregulated, which leads to aberrant proliferation and neoplastic transformation since p53 is a repressive regulator of cell growth 48 . Researches have shown that aberrant p53 expression is directly related to tumor lymphovascular invasion, clinical stage, and clinicopathology in malignant cells 49,50 . But it is still unknown how aberrant p53 expression influences PC cells' malignant growth, metastasis, and differentiation.…”
Section: Resultsmentioning
confidence: 99%